The Role of Social Capital in Community Based Ecotourism: A Case of Batang District, Central Java, Indonesia - Widiartanto; Fendy Eko Wahyudi; R. Slamet Santoso Santoso; Priyotomo (Research Horizon, 2022)
This study explores the role of social capital in developing local community-based tourism innovation villages. Social capital, including social networks, beliefs, norms of reciprocity, and local cultural values, ​​is a vital asset in various local community development programs. Social capital will be reflected in the community's ability to work together, generate awareness and commitment, a sense of belonging, and social solidarity, and create active participation in achieving common goals. Its presence and role in society are crucial for the success of community development goals and programs, including the eco-tourism development program. This study used a qualitative approach based on a case study located in Batang Regency, Central Java, and conducted in-depth interviews with selected informants. The results show that social capital encourages the ability and capability of local communities to work together and coordinate to contribute to the sustainability of ecotourism productivity significantly. In particular, social capital impacts the readiness and knowledge of local communities on tourist villages, socio-environment, and economy. A part from the active participation of the local community in planning, implementing, and maintaining the tourism village and planning strategies to initiate community action, is an important factor in the sustainability of ecotourism management. In conclusion, several recommendations need to be proposed, including the cooperation of the local community with the Batang Regency Tourism and Culture Office. In addition to collaborating with private investors in order to develop tourism potential in Deswita Pandansari with a mutually beneficial cooperation pattern (mutual benefit). It is especially for the development of traditional arts in order to integrate local arts to support tourist destinations in Pandansari.